Effect of Pyrolysis Atmosphere and Electrolyte pH on the Oxygen Reduction Activity, Stability and Spectroscopic Signature of FeNx Moieties in Fe-N-C Catalysts. Issue 7 (1st January 2019) - Santori, Pietro Giovanni; Speck, Florian Dominik; Li, Jingkun; Zitolo, Andrea; Jia, Qingying; Mukerjee, Sanjeev; Cherevko, Serhiy; Jaouen, Frédéric
Abstract : Two Fe-N-C catalysts comprising only atomically-dispersed FeNx moieties were prepared, differing only in the fact that the second catalyst (Fe0.5 -NH3 ) was obtained by subjecting the first one (Fe0.5 -Ar) to a short pyrolysis in ammonia. While the initial ORR activity in acid medium in rotating disk electrode is similar for both catalysts, the activity in alkaline medium is significantly higher for Fe0.5 -NH3 . Time-resolved Fe dissolution reveals a circa 10 times enhanced Fe leaching rate in acidic electrolyte for Fe0.5 -NH3 relative to Fe0.5 -Ar. Furthermore, for the former, the leaching rate is strongly enhanced when the electrochemical potential is in the range 0.75–0.3 V vs. RHE. This may explain the reduced stability of ammonia-pyrolyzed Fe-N-C catalysts in operating PEMFCs. In alkaline medium in contrast, Fe0.5 -NH3 is more active and more stable, with minimized Fe leaching during electrochemical operation in load-cycling mode. Operando X-ray absorption spectroscopy measurements in alkaline electrolyte reveals similar trends of the XANES and EXAFS spectra as a function of the electrochemical potential for both catalysts, but the magnitude of change is much less for Fe0.5 -NH3, as evidenced by a Δμ analysis. This is interpreted as a lower average oxidation state of FeNx moieties in Fe0.5 -NH3 at open circuit potential.